Biophysical Approaches for Applying and Measuring Biological Forces. Issue 5 (19th December 2021) - Sun, Wenxu; Gao, Xiang; Lei, Hai; Wang, Wei; Cao, Yi
Abstract: Over the past decades, increasing evidence has indicated that mechanical loads can regulate the morphogenesis, proliferation, migration, and apoptosis of living cells. Investigations of how cells sense mechanical stimuli or the mechanotransduction mechanism is an active field of biomaterials and biophysics. Gaining a further understanding of mechanical regulation and depicting the mechanotransduction network inside cells require advanced experimental techniques and new theories. In this review, the fundamental principles of various experimental approaches that have been developed to characterize various types and magnitudes of forces experienced at the cellular and subcellular levels are summarized. The broad applications of these techniques are introduced with an emphasis on the difficulties in implementing these techniques in special biological systems. The advantages and disadvantages of each technique are discussed, which can guide readers to choose the most suitable technique for their questions. A perspective on future directions in this field is also provided. It is anticipated that technical advancement can be a driving force for the development of mechanobiology. Abstract : To gain further insight into how living cells sense and respond to mechanical stimuli, advanced approaches have been developed, including traction force microscopy (TFM), atomic force microscopy (AFM), magnetic tweezer (MT), optical tweezer (OT), molecular force probe (MFP), and micropipette aspiration (MPA). A brief introduction of these techniques can contribute to the investigation of mechanobiology in more detail.